Characteristics of patients complaining of halitosis and factors associated with halitosis. (19th November 2013) - Lu, H‐X; Tang, C; Chen, X; Wong, MCM; Ye, W
<x xml:space="preserve">Abstract</x> Objectives To describe the characteristics of patients who visited halitosis clinic and to investigate the factors that may associate with halitosis. Materials and Methods Nine hundred and eleven patients, who visited halitosis clinic for consultations, underwent organoleptic tests and volatile sulfur compound (VSC) measurements with a portable sulfide monitor. The oral health of patients, including dental caries, oral hygiene, and gingival inflammation status, was assessed. Questionnaires were used to obtain information on demographics, oral hygiene practices, and dietary habits. Results Of the 911 patients, more females than males visited the clinic. Patients' age ranged from 18 to 82 years (mean ± s.d.: 40.8 ± 14.1). Almost 30% of patients had complained of halitosis for over 5 years before looking into treatments. Approximately half of the patients self‐perceived that they were unable to get close to others. Around 77% of patients had halitosis. Results of multiple logistic regressions for organoleptic scores and VSC values showed that tongue coating and tongue scraping were significantly associated with halitosis (P < 0.05). Conclusions Among these Chinese patients, over three‐quarters of patients had halitosis, and negative impacts on social communications were observed. Tongue coating was the most important factor responsible for halitosis.